EFFECTS OF Bruguiera gymnorrhiza MANGROVE FRUIT FLOUR ON THE SENSORY, PHYSICAL, AND CHEMICAL CHARACTERISTICS OF SNACK BARS - Arisandi, Desy; Puspitasari, Yunita Eka; Romadhon, Haydar Zakaryya; Sulistiyati, Titik Dwi; Hardoko; Anies Chamidah; Mirza Gulam Ahmad; Perdana, Angga Wira (Fakultas Teknologi Pertanian Universitas Brawijaya, 2026)
The increasing demand for practical, nutritious, and locally sourced food products highlights the need to explore mangrove-based ingredients as functional alternatives in snack formulations. This study investigated the effect of Bruguiera gymnorrhiza fruit flour substitution on the sensory, physical, and chemical characteristics of snack bars to determine the most acceptable formulation based on the overall balance of product quality attributes. Four substitution levels (0%, 5%, 10%, 15%) were tested under a Completely Randomized Design (CRD). Sensory evaluation (n = 50), hardness testing, color measurement (L*, a*, b*, Hue°), proximate composition, caloric value, and carbohydrate content using the Luff–Schoorl method were conducted. The 5% substitution showed the most acceptable overall sensory performance, with the highest scores for color (3.28), aroma (3.24), and texture (3.31), although the control treatment showed the highest taste score. Increasing mangrove flour concentration decreased brightness and yellowness, while increasing redness due to enzymatic and Maillard browning. Hardness rose significantly, reaching 797.60 gf at 15%. The selected 5% formulation, identified as the most acceptable overall treatment, contained 23.79% moisture, 1.57% ash, 9.35% fat, 10.01% protein, 53.55% carbohydrate, and 342.46 kcal. Carbohydrate levels increased progressively across treatments. Overall, Bruguiera gymnorrhiza flour increased energy density while maintaining acceptable product quality, suggesting its potential as a sustainable local ingredient for snack-bar development.